Intersecting Social Science and Conservation - Sanborn, Thomas; Jung, Julia (Frontiers in Marine Science, 2021)
There is a growing consensus that current conservation strategies are unable to cope with the acceleration of human-caused environmental degradation. The philosophies that underpin and shape traditional conservation initiatives have begun to shift toward a “people and nature” approach, based on a new and deeper understanding of relational values. With this shift, there is increasing concern about the social impacts of conservation and a need to consider not only the environmental aspects of conservation, but also issues of equity and social justice. This is especially important for marine conservation to avoid repeating the exclusionary and unjust protective measures sometimes seen in traditional terrestrial conservation. Additionally, lack of compliance with management schemes, and failure to consider the social dimensions and realities of local communities have hindered the success of conservation initiatives. Therefore, increasing engagement with social science and a better understanding of human-wildlife and human-nature connections are necessary. Community-based conservation approaches and payment for ecosystem service schemes can provide important insights and lessons for such improved participatory management. Furthermore, the use of social science offers a range of methods and approaches that can be used to improve the consideration of those social dimensions. These include different theoretical frameworks for understanding the relationships between people, society, and nature, innovative participatory methods and more flexible, adaptive systems-based approaches for understanding complex socio-ecological systems. Increasing and mainstreaming the inclusion of the social dimensions of conservation will also depend on overcoming current institutional barriers such as lack of capacity, time, and funding opportunities especially in the context of marine social science.